Homan's Contemporary Economic Thought - Knight, Frank H.; Homan, Paul T. (Quarterly Journal of Economics, 1928)
Journal Article Homan's Contemporary Economic Thought Get access Frank H. Knight Frank H. Knight The University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 43, Issue 1, November 1928, Pages 132–141, https://doi.org/10.2307/1883943 Published: 01 November 1928